Komunikasi Public Relation Pondok Pesantren Darul Azhar dalam Membangun Citra Postif pada Masyarakat Aceh Tenggara - Helandra, M. Ebi Saluja; Khatibah, Khatibah; Kustiawan, Winda (ANWARUL, 2023)
The purpose of this study was to find out how the public relations communication strategy of Darul Azhar Islamic Boarding School is building a positive image and knowing the supporting factors in communicating through public relations practices that are used as well as knowing the obstacles and solutions to these obstacles in implementing communication. This research was conducted at the Darul Azhar Islamic Boarding School, Jalan Kutacane Blangkejeran, Deleng Megakhe, Southeast Aceh District. This study uses a qualitative research method with a descriptive approach, namely a study that tests it by collecting data, processing, analyzing and manipulating qualitatively and describing or describing a number of variables that are relevant to the problem and unit under study. The informants of this study consisted of 1 leader of the Darul Azhar Islamic Boarding School, 2 people from the Public Relations of the Darul Azhar Islamic Boarding School, 3 people from the Ustad of Darul Azhar Islamic Boarding School, 3 people from the community. Data collection techniques used by observation, interviews, and documentation. The results showed that: The communication strategy for Public Relations of the Darul Azhar Islamic Boarding School in Building a Positive Image of the Southeast Aceh Community, namely knowing the audience as the target of communication, compiling messages to be conveyed to the audience, determining communication methods such as redundancy, namely repeating the message conveyed; canalizing, namely understanding the group that is the target of the communication strategy; informative, namely providing information; persuasive namely influencing and giving; educative namely educating, then the strategy that is carried out is then the selection of media use, and finally the role of the communicator. The Biggest Darul Azhar Islamic Boarding School Public Relations Barrier is the lack of communication and difficulty in expressing Perceptions which hamper the entire communication process. The other obstacles can still be overcome easily.